The Role Of Field Of Study Civics In Improving The Quality Of Education Grade Students VIII SMP Negeri Torgamba, Kabupaten Labuhanbatu Selatan - Syahrizal Efendi Lubis (CV. AFDIFAL MAJU BERKAH, 2022)
This study measured the role of Field of Study Civics in improving the quality of education the students of class VIII SMP Negeri Torgambah, Kab. Labuhanbatu Selatan For learning CIVICS as well as the factors that support and hinder the process of learning the CIVICS in the classroom, this Type of research is qualitative research (qualitative research). Data collection was done by conducting observation, interview, questionnaire, documentation. Data analysis with triangulation and presented qualitatively and analyzed using qualitative analysis. This study aims to describe and analyze critically about the role of field of study CIVICS in improving the quality of the learning interest of the students of Class VIII Smp Negeri Torgambah, Kab. Labuhanbatu Selatan. The results of this study are: (1) the Role of the teacher as the teacher covers the manufacture of the RPP, the Syllabus has been good with orentasi enhance the role of interest in learning CIVICS interpretation of the questionnaire reached to 81.25%. The role of the teacher as the manager of the class, the teacher uses power point, the formation of a study group, (2) Obstacles in the learning of Citizenship Education is the condition of the students who is still unstable because of the age and origin of students who vary with the environmental conditions of different social